2019
DOI: 10.3389/fphar.2018.01539
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Ciji-Hua’ai-Baosheng II Formula on Chemotherapy-Treated H22 Hepatocellular Carcinoma Mouse Model by Promoting Tumor Apoptosis

Abstract: Ciji-Hua’ai-Baosheng II Formula (CHB-II-F) is a traditional Chinese medical formula that has been shown in clinical practice to relieve side effects of chemotherapy and improve quality of life for cancer patients. In order to understand the mechanism of its protective effects on chemotherapy, mice with transplanted H22 hepatocellular carcinoma were employed in this study. Ninety-two mice were injected subcutaneously with H22 HCC cell suspension into the right anterior armpit. After mice were treated with 5-flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…e Ciji-Hua'ai-Baosheng decoction is a TCM formula introduced in recent years to treat cancer patients and contains five main compounds: Radix Salviae Miltiorrhizae, Codonopsis Radix, Poria, Bulbus Fritillariae Ussuriensis, and Concha Ostreae [56,57]. Ciji-Hua'ai-Baosheng granules can prolong the survival of HCCbearing mice receiving chemotherapy [105].…”
Section: Formulas Upregulate Immunostimulatory Factors Tomentioning
confidence: 99%
“…e Ciji-Hua'ai-Baosheng decoction is a TCM formula introduced in recent years to treat cancer patients and contains five main compounds: Radix Salviae Miltiorrhizae, Codonopsis Radix, Poria, Bulbus Fritillariae Ussuriensis, and Concha Ostreae [56,57]. Ciji-Hua'ai-Baosheng granules can prolong the survival of HCCbearing mice receiving chemotherapy [105].…”
Section: Formulas Upregulate Immunostimulatory Factors Tomentioning
confidence: 99%
“…Previous animal experiments showed that CHB-II-F had little side effect and could increase the weight of mice after tumor chemotherapy. In combination with 5-FU, the inhibition of tumor cells may be enhanced by promoting apoptosis of tumor cells and regulating the expression of tumor apoptosis factors ( Fu et al, 2018 ; Fu et al, 2019 ). The purpose of this study was to explore the therapeutic effect and mechanism of CHB-II-F on loss of appetite after chemotherapy in H 22 transplanted tumor mice and to provide more experimental evidence for its clinical application.…”
Section: Introductionmentioning
confidence: 99%